2021
DOI: 10.1152/ajpheart.00608.2020
|View full text |Cite
|
Sign up to set email alerts
|

The transient outward potassium current plays a key role in spiral wave breakup in ventricular tissue

Abstract: Spiral wave reentry as a mechanism of lethal ventricular arrhythmias has been widely demonstrated in animal experiments and recordings from human hearts. It has been shown that in structurally normal hearts, spiral waves are unstable, breaking up into multiple wavelets via dynamical instabilities. However, many of the second-generation action potential models give rise only to stable spiral waves, raising issues regarding the underlying mechanisms of spiral wave breakup. In this study, we carried out computer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…In a previous study, 16 we showed that I to could destabilize spiral wave reentry, causing spiral wave breakup. Here, we show that the late I to stabilizes reentry and can prevent the spiral wave breakup caused by the peak I to .…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…In a previous study, 16 we showed that I to could destabilize spiral wave reentry, causing spiral wave breakup. Here, we show that the late I to stabilizes reentry and can prevent the spiral wave breakup caused by the peak I to .…”
Section: Resultsmentioning
confidence: 79%
“…Besides suppressing the genesis of P2R, late I to can also prevent spiral wave breakup. We showed in a previous study 16 that I to could promote spiral wave breakup by steepening the APD restitution curves. Besides the steep APD restitution-induced breakup, we also observed P2Rs resulting from the complex wave dynamics, giving rise to a mixture of spontaneous firings (P2Rs) and spiral wave reentry (Figure S7 and Videos S3 and S4).…”
Section: Roles Of Late I To On P2r Formation and Stabilitymentioning
confidence: 79%
See 1 more Smart Citation
“…They found that these suppressions led to different alterations in APD [ 38 ]. Additionally, Landaw et al demonstrated through multiple simulation models the significant influence of the transient outward potassium current in initiating the fragmentation of spiral waves [ 40 ]. Therefore, it can be deduced that alterations in various potassium ion currents in different models lead to varying effects on the formation of spiral waves and turbulent states.…”
Section: Introductionmentioning
confidence: 99%
“…The (endocardial) TP06 cardiac cell model [14], which is based on the TNNP04 model [15], is by now a well-established and much studied cardiac cell model [9][10][11][12][13]16]. Despite that, a Email address: andre.erhardt@wias-berlin.de (André H. Erhardt) rigorous mathematical analysis of all its dynamics is still lacking.…”
Section: Introductionmentioning
confidence: 99%